Structuring of Reasoning Process Scientific Explanation through a Multimodal Classroom Discourse - Lee, J.; Tang, Kok-Sing (2016)
It is recognised that the nature of talk between teachers and students is highly significant that seeks to assist students in the learning, reasoning and knowledge building. The ability of student to generate a sound explanation is a hallmark of meaningful understanding and is definitely one of the desirable skills specific to Science discipline. While multimodality is inherent in science classroom teaching and learning, much attention has been drawn to how the range of different modes make meaning beyond language in classroom teaching. However, not much research was done to understand how science teachers structure the reasoning process in a scientific explanation through the use of multimodality. In this paper, reasoning process refers to the deliberative thinking that involves consideration of science content knowledge or contextual information to construct the canonical scientific explanation for a question. Video data of classroom teaching of a Physics teacher in a secondary school was analysed to investigate how the teacher structure the conceptual understanding and the reasoning process required to construct scientific explanation. Through a multimodal analysis and micro-discursive analysis of the teacher-led discussion, it was found that the modelling of the reasoning process was implicitly embedded in two common practices: (i) sequential translation of multiple representations and (ii) using discursive techniques to link up the rhetorical parts of the explanation. Based on the findings, future possibilities and suggestions of connecting multimodality to reasoning skills for both research and practice are discussed.